Ratio Material Learning Design Using the Context of Cooking Rice to Help Elementary Students Understand Concepts - Filian Yunita Sari; Zulkardi; Ratu Ilma Indra Putri; Ely Susanti; Duano Sapta Nusantara (Jurnal Inovasi Matematika, 2024)
Understanding concept is something that students need to have because the concepts in mathematics material are interconnected with each other. The purpose of this research is to determine the learning design of ratio material using the context of cooking rice which can help elementary school students understand the concept of ratio. Researchers designed student activity sheets using the context of cooking rice before conducting research. This design research was carried out on class VI students at one of SD Negeri in Belitang and was carried out in three stages, namely the preparing for the experiment, the design experiment, and retrospective analysis. Data collection through student activity sheets and interviews. Miles and Huberman techniques are used to analyze data which includes data reduction, data presentation, and data conclusion. The results showed that ratio material learning design using the context of cooking rice can help students understand the concepts of ratio. The learning track consists of four activities, namely (1) watching videos of cooking rice, (2) determining the relationship between the amount of rice and the amount of water in the process of cooking rice, (3) making a comparison table of the amount of rice and the amount of water needed to cook rice, (4) conclude the meaning of ratio based on the activity of cooking rice.